PENGARUH STRUKTUR MODAL DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SUB SEKTOR PLASTIK DAN KEMASAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Grace, Ernest; Nainggolan, Christine Dewi; Manurung, Sepbeariska (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2020)
This research aims to determine the influence of profitability on firm value and profitability on firm value in plastic and packaging Sub Sector Companies Listed on The Indonesia Stock Exchange. The type of data research is secondary data and sampling method that used is purposive sampling. Data collection by observation and documentation. The analysis technique use descriptive qualitative and quantitative. The research results show that capital structure does not effect the firm value and profitability has possitive and significat effect on firm value. Simultaneously, capital structure and profitability are have positive and significant effect on firm value.